COPROPHILOUS FUNGAL COMMUNITY OF WILD RABBIT IN A PARK OF A HOSPITAL (CHILE): A TAXONOMIC APPROACH - Piontelli L., Eduardo; Cruz C, Rodrigo; Toro .S.M., M. Alicia (Boletín Micológico, 2006)
During year 2005-through 2006 a study on coprophilous fungal communities present in wild rabbit dung was carried out in the park of a regional hospital (V Region, Chile), 21 samples in seven months under two seasonable periods (cold and warm) being collected. Sixty species and 44 genera as a total were recorded in the sampling period, 46 species in warm periods and 39 in the cold ones. Major groups were arranged as follows: Zygomycota (11,6 %), Ascomycota (50 %), associated mitosporic genera (36,8 %) and Basidiomycota (1,6 %). Ascomycetes genera having the highest occurrence were: Chaetomium (5), Saccobolus and Sordaria (3) Podospora, Schizothecium and Sporormiella (2). Constant and dominant species were : Chaetomium cuniculorum, Ch. murorum, Coprinus spp., Iodophanus carneus, Pilaira anomala, Schizothecium tetrasporum, Sordaria humana, Sporormiella teretispora and Stilbella fimetaria. Under a taxonomic approach focused on the majority of meiosporic fungi (Ascomycota), the presence of new records of fungi for Chile is emphasized: Fusariella hughesii, Neurospora caulospora, Pleuroascus nicholsonii, Rhytidospora bispora, Saccobolus globuliferellus, among others.